Degradation of chloramphenicol using Ti‐Sb/attapulgite ceramsite particle electrodes. (13th April 2019) - Sun, Yongjun; Chen, Aowen; Zhu, Sichen; Sun, Wenquan; Shah, Kinjal J.; Zheng, Huaili
Abstract: Ti‐Sb/attapulgite ceramsite particle electrodes were prepared for the efficient degradation of chloramphenicol (CAP) in wastewater. To observe the surface morphology and structural characteristics of the Ti‐Sb/attapulgite ceramsite particle electrodes, Fourier transform infrared spectroscopy, X‐ray fluorescence, scanning electron microscopy, and X‐ray diffraction were used for characterization. Parameters affecting the degradation efficiency and the energy consumption of the Ti‐Sb/attapulgite ceramsite particle electrodes, such as current density, electrode distance, initial pH, conductivity, air flow, and packing ratio, were examined. Results showed that the optimal conditions were 20 mA/cm 2 current intensity, 3 cm electrode distance, 5, 000 μS/cm conductivity, 2.0 L/min air flow, 50.0% packing ratio, and initial pH 1. The removal efficiency of chloramphenicol was 73.7% under the optimal conditions, and the energy consumption was 191.3 (kW h)/kg CAP. Practitioner points: Attapulgite ceramsite with good physical performance was prepared. The removal efficiencies for CAP in water by Ti‐Sb/attapulgite ceramsite particle electrodes were studied. CAP was effectively removed by 3‐D electrode system. CAP removal was significantly influenced by operational parameters. Three‐dimensional electrode system shows good degradation ability. Abstract : Efficiently removing CAP in water by Ti‐Sb/attapulgite ceramsite particle electrodes.